Implementasi Pendidikan Inklusif di UPT SPF SMPN 3 Makassar - Aisyah Dwi Rahmawati; Arismunandar; Ahlun Ansar; Aulia Gita Cahyani Nur; Winda (Jurusan Pendidikan Luar Biasa, 2026)
Inclusive education aims to ensure equal access to education for all students, including those with special needs. This study aims to analyze the implementation of an inclusive education model at UPT SPF SMP Negeri 3 Makassar as a pilot school since 2013. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the school implements an admission policy allocating approximately 2% of seats for students with special needs and integrates them into regular classrooms through adaptive learning practices. The implementation is supported by collaboration among teachers, parents, and partner institutions such as PUSPAGA. However, several challenges persist, including the limited number of special education teachers, inadequate disability-friendly facilities, and low awareness among some parents regarding inclusive education. The study concludes that SMP Negeri 3 Makassar represents a good practice of inclusive education at the junior secondary level. Therefore, improving infrastructure and providing continuous teacher training are recommended to sustain and enhance the quality of inclusive education services.